The turkic identity in the novel «Death of the grey fierce» by the turkish writer Kh. N. Atsyz - Abeldaev, Zh. (Journal of Oriental Studies, 2021)
Turkish writer Hussein Nihal Atsyz began writing historical novels in the middle of the 20th century. His historical dilogy "Fierce Gray" had a significant impact on the self-consciousness of the Turkish society, illuminating the deep layers of history. The power and desire for stability of the great states founded by theTurks is proved through historical facts and interpreted by a high artistic style. The first book of the historical dilogy "Fierce Gray" by Kh.N.Atsyz is called "Death of the Fierce Gray". The storyline of the story described in the novel is the foundation of the Turkic Khaganate, its division into two parts, and the fierce struggle that this state waged against the Chinese dynasties. The struggle against the Chinese armies, in which success was on the side of the Turks, then on the side of their enemiesin a fierce battle, is described reliably and without embellishment. The author describes in an artistic form the heroism of the ancient Turks, who, despite the stubbornness and cunning of a strong enemy, not only fought for the land, but also tried to preserve their Turkic identity. The article deals with the question of the specific content of the concept of Turkic identity in the historical novel "Death of the Fierce Gray" by Hussein Nihal Atsyz.